A discourse analysis of lecturer identities in classroom interactions - Azizan, Mazlin (2019)
This study examines the construction of lecturer identities and how power is manifested through an analysis of interactional classroom strategies adopted by lecturers in creating effective teaching and learning environments. A series of ethnographic case studies of award-winning lecturers were conducted at a Russell group university in the UK. The ethnographic approach entailed participant observation of classroom discourse, interviews with lecturers and their students, the production of detailed field notes, and a series of written textual data including student evaluations of teaching, student evaluations of modules and Teaching Philosophy statements from lecturers themselves. Through an overarching sociolinguistic approach, an integrated analytical framework consisting of Critical Discourse Analysis and Positive Discourse Analysis, influenced by Interactional Sociolinguistics, Politeness Theory and Community of Practice, has been adopted, where data analysis at macro and micro levels has taken place, following Geertz’s (1973) highly influential principles of ‘thick description’ for conducting effective ethnography. The findings demonstrate the range of interactional classroom strategies used by the award-winning lecturers, analyzed in the openings and closings in their classroom discourse, along with a detailed analysis of the type, range and multifunctionality of humour. The ethnographic approach demonstrates the emergence and constructions of their professional identities and power, materialized through politeness and relational devices in creating good rapport, maintaining positive relationships with their students and above all, creating, maintaining and facilitating effective teaching and learning opportunities.